The Pakistan Army 1966-71 - Shaukat Riza, Major General (Retd.) (GHQ, Rawalpindi Army Education Press, 1990)
This books covers the army activities between the years of 1966 to 1971.
Include Annexure, Bibliography, Epilogue and Index
Keywords: Pakistan. Army -- Pakistan, Military